What affect heart in SAM: structure or function - Sharma, Ashutosh Kumar; Gaur, Ajay; Sharma Agrawal, Neetu (International Journal of Contemporary Pediatrics, 2017)
Background: Objective of present study was to assess structural and functional cardiac changes in children with severe acute malnutrition between the age of 6 month to 59 months. Setting: The study conducted in Department of paediatrics, Kamla Raja Hospital, Gajra Raja Medical College, Gwalior. A prospective case control study. Participants: 100 cases and 100 controls enrolled based on the selection criteria, Control group was selected from patient came in Out Patient Department. Children from 6 months to 59 months of age with weight for height ranging <-3SD and/or Mid Upper Arm Circumference (MUAC) <11.5 cm and/or edematous malnutrition and/or visible severe wasting). Selection of cases and control were done through random sampling method. Methods: All enrolled admitted children were stabilised after admission as per WHO protocol of management. After that they undergone echocardiographic and electrocardiographic evaluation and data were collected and Analysed. Results: In this study, study group show decrease in dimension of heart i.e. IVSd (p-value-0.02413), LVEDd (p-value-0.0000017), PLVWd (p-value-0.01493), LVEDs (p-value-0.0000263), PLVWs (p-value-0.0000254) more affected during diastole than systole, increased HR (p-value-0.0044), shorten PR intervals (p-value-0.0001) and shorten P wave(p-value-0.000385), QT (p-value-0.044) and QTc (p-value-0.00968) as compared to control group. Pericardial effusion found in 16 cases in study group (8 mild and 8 trace). Conclusions: Early evaluation of cardiac function in malnourished child will significantly affect the management of Severe Acute Malnutrition to prevent deaths from Severe Acute Malnutrition.